Traditional uses of medicinal plants practiced by the indigenous communities in Gurage Zone, south central Ethiopia - Teka, Alemtshay; Asfaw, Zemede; Demissew, Sebsebe; Van Damme, Patrick (Ethnobotany Research and Applications, 2020)
Background: The traditional use of medicinal plants for curing and preventing illnesses has been paramount and widely practiced in Ethiopia for generations. This study was carried out in Gurage zone, Southern Nations, Nationalities and Peoples Region, Ethiopia. The study aims to document the state of traditional knowledge related to local plant uses for medicine and examine how the communities’ value and relate to medicinal plants. Methods: Ethnobotanical data were collected using semi-structured interviews, in which 240 informants were involved. For data analysis, descriptive statistics and ethnobotanical indices, including informant consensus factors (ICF) and use preference were used. Results: A total of 200 medicinal plant species that are used to treat human ailments were documented. Plant families Asteraceae (13%) and Lamiaceae (10%) were predominant whereas the most frequently used plant parts were the leaves, accounting to about 43.8% followed by roots (14%). Indigenous knowledge distribution in the community showed significant differences (p < 0.05) in the study groups for factors of age and educational level. The ICF value obtained which ranges between 0.49 and 0.92 indicates the presence of good agreement among the informants regarding therapeutic uses of reported medicinal plant species. More than 50% of the respondents prefer to use traditional medicine as the first line of treatment. For eight health problems traditional herbal medicines remain dominant and highly preferred treatment, irrespective of the presence of modern health services within short distance from their residence. Conclusions: The richness of medicinal plant species recorded from the study area reflects the dependence of the communities on plant resources of their natural surroundings. Combined effect of various threatening factors are posing threat as a result widely used medicinal plants are becoming locally rare which calls for protecting and developing the resource for wider and better use. Keywords: Gurage, medicinal plants, traditional knowledge